Temperature-dependent bending strength in piezoelectric semiconductive ceramics - Zhao, M.H.; Wang, Y.; Guo, C.K.; Lu, Chunsheng; Xu, G.T.; Qin, G.S. (Elsevier, 2021)
By using theoretical analysis and three-point bending experiments, influence of temperature on the bending strength of GaN ceramics is investigated. Based on the critical fracture energy density, a simple and effective temperature-dependent bending strength prediction model is established for piezoelectric semiconductive ceramics. In the model, the bending strength at high temperature depends on the reference temperature, stiffness, polarization and melting point, as well as piezoelectric polarization charges. It is shown that the theoretical predictions are consistent with experimental results. Thus, such a model is instructive to the reliability design of GaN high-temperature devices.